P‐49: TFT‐LCD Advanced Adaptive De‐mura System. Issue 1 (29th May 2019) - Zhao, Wenqin; Chen, Wei; Ji, Feilin; Lin, Boshen; Chen, Zhenghong
Abstract : In the process of producing TFT‐LCD, the difference in process and material causes the uneven brightness of the panel. In this paper, a system architecture and algorithm are proposed to eliminate the uneven brightness of TFT‐LCD's display, which is called the De‐mura system to improve the quality of the TFT‐LCD.